Oxidative stress and histological changes following exposure to diamond nanoparticles in the freshwater Asian clam Corbicula fluminea (Müller, 1774) - Cid, António (2016)
Recently, the scientific community became aware of the potential ability of nanoparticles to cause toxicity in living organisms. Therefore, many of the implications for aquatic ecosystems and its effects on living organisms are still to be evaluated and fully understood. In this study, the toxicity of nanodiamonds (NDs) was assessed in the freshwater bivalve (Corbicula fluminea) following exposure to different nominal concentrations of NDs (0.01, 0.1, 1, and 10 mg l-1) throughout 14 days. The NDs were characterized (gravimetry, pH, zeta potential, electron microscopy, and atomic force microscopy) confirming manufacturer information and showing NDs with a size of 4–6 nm. Oxidative stress enzymes activities (glutathione-S-transferase, catalase) and lipid peroxidation were determined. The results show a trend to increase in GST activities after seven days of exposure in bivalves exposed to NDs concentrations (>0.1 mg l-1), while for catalase a significant increase was found in bivalves exposed from 0.01 to 1.0 mg l-1 following an exposure of 14 days. The histological analysis revealed alterations in digestive gland cells, such as vacuolization and thickening. The lipid peroxidation showed a trend to increase for the different tested NDs concentrations which is compatible with the observed cellular damage.